การพัฒนาระบบขนถ่ายดีเอ็นเอโดยใช้อนุภาคนาโนไคโทซานและการเหนี่ยวนำให้เกิดกระบวนการออโต้ฟาจีในเซลล์นำเสนอแอนติเจน : โครงการวิจัย - ธนาภัทร ปาลกะ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
Transfection of plasmid containing an insert into cells is an essential step in various application in biomedicine such as gene therapy and DNA vaccine. Most cells take up plasmids with varying efficacy. Antigen presenting cells (APCs) such as dendritic cells and macrophages are one of the hardest cells to transfect. These cells play important roles in antigen presentation to helper T lymphocytes to initiate effective adaptive immune response. In order to induce effective immune response upon vaccination, antigens can be targeted to antigen presenting cells. DNA vaccine is a novel type of vaccine with potentials to replace currently in use vaccine because of its ease in preparation, stability and cost effectiveness. In general, DNA vaccine is administered via intradermal or intramascullar and believed to be taken up by any cells. Specifically targeting DNA vaccine to specific cells are ideal in order to induce optimal immune response. Autophagy is a cellular defense mechanism to target intracellular antigens, including pathogens. Parts of degraded protein antigens are presented to helper T cells. Therefore, in this study, we aimed at developing DNA plasmid delivery system targeting APCs using chitosan nanoparticles and incorporating autophagy inducing system upon DNA delivery, using autophagy inducing plasmid. First, we optimized the transfection using acid soluble chitosan particles that encapsulated DNA plasmid in vitro. At N/P ratio of 8:1-10:1 yielded the highest transfection rate in HEK293T. We modified chitosan to contain strepavidin and encapsulated plasmid DNA. The step was foolowed by incubation of chitosan-strepavidin-DNA plasmid with biotinylated anti-F4/80 antibody that specifically targeting macrophages. Unexpectedy, modified chitosan incubated with anti-F4/8 antibody did not increase the numbers of transfected macrophage cell line, RAW264.7. These results imply that it is necessary to further study in optimization in using strepavidin-modified chitosan for target cell specific DNA plasmid delivery. In addition, in order to increase antigen presentation to T cells, we developed a DNA plasmid system which induced cells to undergo autophagy. Using plasmid containing mutated mTOR gene encoding inactive mTOR kinase, autophagy could be detected in HeK293T and dendritic cell line, JAWSII. Therefore, autophagy inducing system is established. Combining these techniques, it is possible to use DNA vaccine to induce robust immune response.